The Type VI Secretion System: A Dynamic System for Bacterial Communication? - Gallique, Mathias; Bouteiller, Mathilde; Merieau, Annabelle (Frontiers in Microbiology, 2017)
Numerous studies in Gram-negative bacteria have focused on the Type VI Secretion Systems (T6SSs), Quorum Sensing (QS), and social behaviour, such as in biofilms. These interconnected mechanisms are important for bacterial survival; T6SSs allow bacteria to battle other cells, QS is devoted to the perception of bacterial cell density, and biofilm formation is essentially controlled by QS. Here, we review data concerning T6SS dynamics and T6SS–QS cross-talk that suggest the existence of inter-bacterial communication via T6SSs.